Integrative Metabolome and Transcriptome Analyses Reveal the Pericarp Coloration Mechanisms in Bitter Melon (Momordica charantia L.) - Liang Yang; Zhi Li; Ju Li; Yanqin Ma; Mingjun Miao; Haicheng Long; Yujie Zhou; Wei Chang (Horticulturae, 2024)
Pericarp colors are critical agronomic traits that affect the quality and economic values of fruits. Although a diversity of bitter melon pericarp (BMP) colors is available, the fruit pigmentation mechanisms remain elusive. Hence, this study aimed to unveil the key metabolites and molecular mechanisms underlying variation in BMP coloration through integrative metabolomics and transcriptomics analyses of four differently colored genotypes, including K1102 (grayish orange), 262 (grayish yellow), 1392 (very soft green), and K115 (dark grayish cyan). The four BMPs exhibited significant metabolite profile and transcriptional differences, as over 112 and 1865 DAMs (differentially accumulated metabolites) and DEGs (differentially expressed genes), respectively, were identified. The variation in the content of six anthocyanins, including malvidin 3-O-glucoside, petunidin 3-O-glucoside, rosinidin O-hexoside, cyanidin, cyanidin 3-p-hydroxybenzoylsophoroside-5-glucoside, and pelargonidin 3-O-beta-D-glucoside, might be the major driving factor of BMP color changes. Notably, malvidin 3-O-glucoside, rosinidin O-hexoside, and petunidin 3-O-glucoside are the dominant pigments in K115, while carotenoids and other flavonoids may contribute to other colors. Candidate flavonoid structural and regulatory (MYBs, NACs, MADSs, bHLHs, and bZIPs) genes were identified. Of them, gene13201 (anthocyanin reductase), gene8173 (polyphenol oxidase), gene2136 (NAC43), gene19593 (NAC104), and gene15171 (tetrapyrrole-binding protein) might play essential roles in K115 pericarp color development. Our findings deepen our understanding of BMP pigmentation and provide fundamental resources for higher-valued bitter melon breeding perspectives.